AI-Enhanced Legal Translation: A Bibliometric Analysis of Global Research Trends: الترجمة القانونية المعززة بالذكاء الاصطناعي: تحليل بيبليومتري لاتجاهات البحث العالمية - Kada, AFIA (Maalim, 2026)
This study aims to explore the trajectory of scholarly trends concerning the topic of artificial intelligence in legal translation, in order to facilitate understanding of future directions in academic interest on this subject. A bibliometric and content analysis was conducted based on the PRISMA framework, supported by the VOSviewer software. The study examined all research published from 1975 to 2025, analyzing a set of 400 publications up to 2025, as documented in the Scopus database. The findings of this review identified the most significant topics addressed by the journals, as well as the leading countries, academic institutions, journals, and authors.